Cash Assistance Program and Consumption Pattern Among Indonesians - Dwiputri, Inayati Nuraini; Kusufi, Muhammad Syam; Ilyas, Ilyas (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360), 2023)
Poverty and households’ economic fragility have been a concern among Indonesian, and the government has addressed this issue by granting a cash assistance program. There will be some effects related to the program. Therefore, this study identifies the effect of cash assistance program on consumption changes among Indonesian as the measurement for public welfare. This paper can be a reference to determine the nexus between transfers and attempting to improve public welfare. This study used Indonesian Family Life Survey (IFLS) as longitudinal datal, and controlled the respondent’s characteristics and adopted the fixed effect at the village level as an estimation technique. The results reveal that, generally, there was a decline in food expenditure that is followed by changing consumption behavior among Indonesian, and the cash assistance program has contributed remarkably to this change. The finding also notes that the objectives of the cash assistance program have not been appropriately achieved as predicted. JEL Classification: H24, I38, O21